The house that screamed - Tébar, Juan 1941-; Ríos, Waldo de los 1934-1977 (Metro-Goldwyn-Mayer Studios, 2023)
"Ein elternloses Mädchen wird Anfang der 20. Jahrhunderts in ein abgelegenes französisches Internat für schwererziehbare Zöglinge gebracht, in dem die Leitung mit brutaler Zucht auf die Einhaltung strengster Disziplin besteht. Doch in dem weitläufigen Anwesen lauert eine weit größere Gefahr, da es ein unheimlicher Killer auf die Mädchen abgesehen hat. Mit suggestiven Bildern und gruseliger Musik entfaltet der Psychothriller ein meisterhaftes Schauerstück auf der Bühne eines gotischen Mädchenpensionats." [filmdienst.de]
Original: Spanien 1969
Special edition contents: brand new 2K restoration from the original negative by Arrow Films ; High Definition (1080p) Blu-ray presentations of the 105-minute uncut version titled The finishing school (La Residencia), and the 94-minute US theatrical version titled The house that screamed, via seamless branching ; original lossless English mono audio on both versions, and lossless Spanish audio on the uncut version ; optional English subtitles for the deaf and hard-of-hearing on both versions, and optional English subtitles for the Spanish audio ; brand new audio commentary by critic Anna Bogutskaya ; This boy’s innocence, a previously unreleased interview with actor John Moulder-Brown ; archive interview with Mary Maude, from the 2012 edition of the Festival of Fantastic Films ; All about my "Mama", a brand new interview with Juan Tébar, author of the original story ; The legacy of terror, a brand new interview with the director’s son, Alejandro Ibáñez ; Screaming the house down, a brand new interview with Spanish horror expert Dr Antonio Lázaro-Reboll, discussing the history of the film and its director ; alternative footage from the original Spanish theatrical version ; original trailers, TV and radio spots ; image gallery ; reversible sleeve featuring original and newly commissioned artwork by Colin Murdoch
Bildformat 2.39:1
Keywords: Film; Blu-Ray-Disc